Faculdade de Educação da UFMG: história e memória (1968-1975) - Nelma Marçal Lacerda Fonseca (2022)
The research aimed at investigating the constitution and institutionalization process of the School of Education of Federal University of Minas Gerais (FaE/UFMG), between 1968 and 1975. The methodology used was based on the analysis of bibliographic, documental and oral sources, pertaining to two central events in the creation of the School of Education: the UFMG Reform Plan, implemented during the administration of Dean Aluísio Pimenta (1964-1967), approved by federal decree number 62.317/68 on February 28, 1968 and in the University Reform of 1968, enacted on November 28, nationwide. Documentary sources are from the academic-scientific and administrative collection of the Research Center, Documentation and Memory (CEDOC/FaE/UFMG). We tried to achieve a more plural history of the School of Education, through the multiple versions of the subjects who experienced the process of these reforms, such as former professors and administrators of the FaE, of the Postgraduate Program in Education (PPGE/FaE) and of former deans of UFMG. The research made it possible to understand what was sometimes heard – “UFMG was ahead of the University Reform of 1968”. The results achieved make it possible to recognize the importance of the School of Philosophy of Minas Gerais as the origin of the Schools and Institutes of UFMG, as they are known today. Above all, it sought to deepen the understanding of the circumstances in which the creation of the FaE took place, the composition of its faculty, its structuring into three Departments - Teaching Methods and Techniques (DMTE), Applied Sciences to Education (DECAE) and of School Administration (DAE), as well as the creation process of the Postgraduate Program. At the national level, the research revealed the social, political, cultural and educational environment of Brazil, Minas Gerais and UFMG, in the studied period.